2019
DOI: 10.4047/jap.2019.11.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polishing systems on roughness and color change of two dental ceramics

Abstract: PURPOSE To evaluate the polishing effect on roughness and color change of pressed and layering ceramics after immersion in coffee solution. MATERIALS AND METHODS 88 ceramic discs (1.0 mm × 10.0 mm) were manufactured - 44 nano-fluorapatite layering ceramics (IPS e.max Ceram. Group C) and 44 pressed lithium disilicate ceramic discs (IPS e. max Press - Group P). Each group was divided into 4 subgroups according to surface treatments: (G) Glaze, (S) Shofu polishing system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…In this study, the value of the ∆E* (2.12) was slightly high (Table 3), and this can be explained by the high degree of fluorosis among the population in Jazan city. Alabdulaaly et al concluded that the fluoride levels in Jazan exceeded the maximum allowed limits [59] Algazali et al performed a clinical in vivo study and found that ∆E* of 2.8 is clinically acceptable [28] [60,61]. This result was close to the value obtained in this study for natural teeth (3.45) (Table 3).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the value of the ∆E* (2.12) was slightly high (Table 3), and this can be explained by the high degree of fluorosis among the population in Jazan city. Alabdulaaly et al concluded that the fluoride levels in Jazan exceeded the maximum allowed limits [59] Algazali et al performed a clinical in vivo study and found that ∆E* of 2.8 is clinically acceptable [28] [60,61]. This result was close to the value obtained in this study for natural teeth (3.45) (Table 3).…”
Section: Discussionsupporting
confidence: 84%
“…It is already known that an increase in roughness and topographical alterations may inherently affect the light transmittance through a restorative material. 21,24,25 The influencing mechanism is explained by the fact that the light direction and incidence is altered when light transmits through a roughened surface, and the material consequently shows opacity, among other optical and colorimetric characteristics (light transmittance and color differences -ΔE 00 ) which may also be altered. It could be accepted that this is the main F I G U R E 3 SEM analysis in a topographic and lateral view of the ceramic surface after surface treatments have been performed…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] These adjustments inherently influence the surface characteristics (topography and roughness features) of ceramics, and in doing so they may potentially change the optical and mechanical properties of these materials. [20][21][22] From this viewpoint, the literature has shown that these procedures may introduce different types of damage/defects into the material's surface, creating different roughness, and surface topography patterns. 18,22,23 It is well-known that an increase in roughness inherently affects the light transmittance through a restorative material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations